Xing Xia Di Tan Decoction Enhances Microwave Ablation and Chemotherapy in Lung Cancer: Molecular Insights from Network Pharmacology - Chen, Peixi; Huang, Junming; Huang, Junming; Du, Shaoshan (Indian Journal of Pharmaceutical Education and Research, 2026)
Background/Aim: Non-small cell lung cancer (NSCLC) accounts for most lung cancer cases and remains a major health burden. Many elderly patients cannot tolerate targeted or immune therapies, or develop resistance, underscoring the need for alternative strategies. This study evaluated the synergistic effects of Xing Xia Di Tan Decoction (XXDTD), a Traditional Chinese Medicine (TCM) formula, with microwave ablation (MWA) and chemotherapy, and explored its molecular mechanisms. Materials and Methods: Network pharmacology was used to identify active compounds and potential targets of XXDTD, followed by pathway enrichment analysis. Experimental validation in A549 NSCLC cells included apoptosis detection (flow cytometry), BAX mitochondrial translocation (Western blot), RXRA expression (qPCR), and proliferation assays (CCK8). RXRA knockdown was performed using siRNA. Results: Network pharmacology identified RXRA, BAX, and CASP3 as key targets involved in apoptosis and chemoresistance pathways. XXDTD treatment increased apoptosis in a dose-dependent manner, promoted BAX mitochondrial translocation, and significantly upregulated RXRA expression. Silencing RXRA reversed XXDTD’s inhibitory effects on cell proliferation and its synergy with cisplatin. The combination of XXDTD and cisplatin showed stronger antiproliferative activity compared with cisplatin alone. Conclusion: XXDTD enhances the efficacy of MWA and chemotherapy in NSCLC by activating BAX-mediated apoptosis and upregulating RXRA, thereby overcoming chemoresistance. These findings support the clinical potential of XXDTD as an adjunct therapy for elderly patients with advanced lung cancer.
Keywords: Lung cancer; Xing Xia Di Tan Decoction; Microwave ablation; Chemotherapy; Network; pharmacology; RXRA; BAX